Examen Especial a Propiedad, Planta y Equipo de L&M de Seguridad Privada Cía. Ltda., Riobamba, período 2022. - Sánchez Narváez, Karla Estefanía (2024)
This research evaluated the "Property, Plant, and Equipment" account of the company L&M de Seguridad Privada Cía. Ltda. for the 2022 period, focusing on compliance with regulations related to the registration, control, and management of its assets. The study employed both deductive and inductive methods, with a documentary and field research design. It adopted a qualitative approach and a descriptive, applicative, and exploratory research level. The research population consisted of documentary records and personnel, and the techniques used included observation, interviews, and surveys. The instruments for data collection were an observation guide, interview guide, and questionnaire. The findings revealed several deficiencies in the control and management of the assets, including outdated regulations, a lack of supporting documentation for approvals and dissemination, the absence of a dedicated department for asset control, and limited physical inspections, which occur only twice a year. In conclusion, the research diagnosed the current state of the company's asset control and management system. While the system is operational, it has significant gaps that should be addressed to improve efficiency and compliance with regulations.